PERBEDAAN USIA, UKURAN MAKROSKOPIS TUMOR, DAN PROFIL HORMON ANTARA PASIEN KARSINOMA TIROID PAPILER KLASIK DAN VARIAN FOLIKULER DI RSUP DR KARIADI SEMARANG - Nabila, Alin; Istiadi, Hermawan; Wikanta, Edmond Rukmana; Miranti, Ika Pawitra; Puspasari, Dik (Medica Hospitalia : Journal of Clinical Medicine, 2021)
Background: New cases of Papillary Thyroid Carcinoma and Carcinoma patients at Dr. Kariadi Hospital, Semarang is quite high, where the most types are Classical Papillary Thyroid Carcinoma and Follicular Variant Papillary Thyroid Carcinoma. On the other hand, in diagnosing PTC, histopathological examination which is a gold standard sometimes has a subjective value. Therefore, it is necessary to have a correlation with the clinical characteristics of the patient in order to get a correct diagnosis. Aim: Understanding the differences in age characteristics, tumor macroscopic size and hormone profile between Classical Papillary Thyroid Carcinoma and Follicular Variant patients at Dr. Kariadi Hospital, Semarang. Method: Analytic observational research with cross sectional design. The number of samples was 38 medical records in which 18 cases of Classic Papillary Thyroid Carcinoma and 20 cases of Follicular Variant Papillary Thyroid Carcinoma. Data with a nominal scale, namely age were analyzed using the Fisher exact test, while the data with a numerical scale, namely the macroscopic size of the tumor and the hormone profile, were tested for normality of Saphiro Wilk then continued with the Mann-Whitney test. Result: Based on the Fisher exact test, there was significant difference (p = 0,009) between age characteristics and Classical Papillary Thyroid Carcinoma and Follicular Variant. In the Mann-Whitney test there was no significant difference (p = 0.3) between the macroscopic size of the classical papillary carcinoma and follicular variant and there was no significant difference TSHs (p = 0.501) and fT4 (p = 0.953) hormone profiles between Classic Papillary Thyroid Carcinoma and Follicular Variants. Conclusion: There was significant difference between the characteristics of age at diagnosis, and there was no significant difference between the macroscopic size of the tumor and the hormonal profile of Classical Papillary Carcinoma and Follicular Variants in Dr. Kariadi Hospital, Semarang.